Landscape complexity promotes resilience of biological pest control to climate change. Issue 1951 (26th May 2021) - Feit, Benjamin; Blüthgen, Nico; Daouti, Eirini; Straub, Cory; Traugott, Michael; Jonsson, Mattias
Abstract : Increased climate variability as a result of anthropogenic climate change can threaten the functioning of ecosystem services. However, diverse responses to climate change among species (response diversity) can provide ecosystems with resilience to this growing threat. Measuring and managing response diversity and resilience to global change are key ecological challenges. Here, we develop a novel index of climate resilience of ecosystem services, exemplified by the thermal resilience of predator communities providing biological pest control. Field assays revealed substantial differences in the temperature-dependent activity of predator species and indices of thermal resilience varied among predator communities occupying different fields. Predator assemblages with higher thermal resilience provided more stable pest control in microcosms where the temperature was experimentally varied, confirming that the index of thermal resilience developed here is linked to predator function. Importantly, complex landscapes containing a high number of non-crop habitat patches were more likely to contain predator communities with high thermal resilience. Thus, the conservation and restoration of non-crop habitats in agricultural landscapes—practices known to strengthen natural pest suppression under current conditions—will also confer resilience in ecosystem service provisioning to climate change.